2013
DOI: 10.1038/srep01437
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of protein glycation using fluorescent phenylboronate gel electrophoresis

Abstract: Glycated proteins are important biomarkers for age-related disorders, however their analysis is challenging because of the complexity of the protein-carbohydrate adducts. Here we report a method that enables the detection and identification of individual glycated proteins in complex samples using fluorescent boronic acids in gel electrophoresis. Using this method we identified glycated proteins in human serum, insect hemolymph and mouse brain homogenates, confirming this technique as a powerful proteomics tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…The interaction of high concentrations of carnosic acid and polydatin and BSA proteins might result in changes in the BSA secondary structure and lower the antiglycation activity (Vlassopoulos et al ., ). Glycated proteins could be considered as an important biomarker for age‐related disorders and helping in identifying biological and physiological entities associated with related diseases (Pereira Morais et al ., ). The results demonstrated that the natural phenolic compounds can become an effective way in preventing protein glycation in the body.…”
Section: Resultsmentioning
confidence: 98%
“…The interaction of high concentrations of carnosic acid and polydatin and BSA proteins might result in changes in the BSA secondary structure and lower the antiglycation activity (Vlassopoulos et al ., ). Glycated proteins could be considered as an important biomarker for age‐related disorders and helping in identifying biological and physiological entities associated with related diseases (Pereira Morais et al ., ). The results demonstrated that the natural phenolic compounds can become an effective way in preventing protein glycation in the body.…”
Section: Resultsmentioning
confidence: 98%
“…Traditionally, glycation has been detected by mass spectrometry or by using anti-AGE antibodies. More recently, a novel technique termed fluorescent phenylboronate gel electrophoresis (Flu-PAGE) has been developed 13 . Flu-PAGE exploits the reversible covalent interaction between boronic acid and cis -diols, that are present in fructosamine-protein adducts in glycated proteins, strengthened by the additional charge interaction between the boronate and the fructosylysine aminogroup 14 .…”
mentioning
confidence: 99%
“…81 The fiber material consists of polyethylene glycol (PEG)-bonded polyacrylamine (PAM) hydrogels and incorporates the same sensor unit. 82 In their smart structure design, polyethylene glycol (PEG)-bonded polyacrylamide (PAM) hydrogel fibers (with better performance than PAM hydrogel fibers) were employed since they can reduce inflammation and continuously respond to blood glucose changes for up to 140 days. The fiber system can be used for long-term in vivo glucose monitoring, and fibers still showed a very strong fluorescence signal through ear skin even one month after implantation (Fig.…”
Section: Polymer-tagged Boronic Acid Probes For Imaging Applicationmentioning
confidence: 99%
“…In addition, Elsen has demonstrated that glycated proteins can be visualised and identified in a variety of complex biological samples, including human serum, Manduca sexta hemolymph and mouse brain cortex homogenates, using fluorescent boronic acids in Flu-PAGE and Flu-BLOT. 82 Benzoxaborole-based probes for imaging applications Dennis Hall pioneered the use of the benzoxaborole 11 (orthohydroxymethyl phenylboronic acid) receptor which has been shown to be a superior receptor unit to the well-established dialkylamino boronic acid (Wulff type, compounds 1-9) analogues. 83 The benzoxaborole 11 unit binds strongly with 4,6-diols and as such can be used to complex strongly with cell-surface glycoconjugates (Scheme 2).…”
Section: Polymer-tagged Boronic Acid Probes For Imaging Applicationmentioning
confidence: 99%